Application of Interpretative Structural Modeling (ISM) to Determine Port Waste Management Strategies for African Swine Fever (ASF) Prevention at Tanjung Priok Port - Novera Nirmalasanti; Effendi, Hefni; Setyowati, Ririn (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2021)
African Swine Fever (ASF) is one of the infectious diseases affecting swine with high mortality rate. Disease transmission occurs direct and indirect. Indirect transmission through feed, virus contaminated object and swill feeding produced by ships. Ships berthing in the port of Tanjung Priok mostly comes or transits from a country which ASF exist. Among those ships, some discharge their garbage and take over into the final dumping site without any further treatment. There are many institution and a third parties involved in garbage management in the port of Tanjung Priok. This research aims is to identify an obstacle, actors and strategies in managing garbage from the ships to prevent ASF spread in the port of Tanjung Priok using Interpretative Structural Modelling (ISM). The results of this research shows the biggest obstacle in managing garbage from the ships, in order to prevent ASF spread in the port of Tanjung Priok is the absence of standard operating procedures (SOP), The most important actor is Indonesia Port Corporation II and the most important strategy is develop an integrated SOP for ship waste management. is to develop an integrated SOP for ship waste management.